Students' Creative Thinking Strategies As High-Level Thinking, Solving Hot Problems In Improving Mathematics Learning - Muhammad Syaiful Islam Al-Ghozi (Al-Makki Publisher, 2024)
Creative Thinking Strategy of Students as Higher-Order Thinking, Solving Hot Problems Under Mathematics Learning Improvement. In our observation during PLP at SMK 2 Pancasila Jember, all students in one flat improved their' creative thinking strategy To improve higher-order thinking in mathematics learning. Therefore, this condition results in an imbalance in learning practices. Thus, this study fills the imbalance gap by describing students' creative thinking strategies as higher-order thinking skills in improving mathematics learning. Results of the study: This can contribute knowledge for educators to manage teaching strategies that can improve mathematics learning, which refers to higher-order thinking skills for all levels of creative thinking. This study is a qualitative descriptive study. The course is SMK 2 Pancasila Jember data collection, a test, observation, and interview. Data analysis is done using the data reduction method, presenting data, and concluding. The results of this study are descriptions of students' creative thinking strategies as higher-order thinking skills in improving mathematics learning, namely students' problems in planning detailed problems; students take time breaks to make a plan, identify the core of the problem, provide original ideas, provide alternative plan solving problems, combine previous ideas with question problems; operate and implement their plans by creating various solution original.